Makna dan fungsi peribahasa arab dalam konteks sosial dan budaya sehari-hari - Azhari, Arina Fitriya (Maliki Interdisciplinary Journal, 2026)
Arabic proverbs are essential elements of social communication that reflect the cultural values and norms of Arab society. Rich in wisdom and brevity, these expressions play a significant role in understanding the Arab worldview. This study aims to explore the meanings and functions of Arabic proverbs in daily life, focusing on their social and cultural contexts. Using a descriptive qualitative approach, the research analyzes commonly used proverbs to uncover their deeper meanings. The findings reveal that Arabic proverbs function not only as communication tools but also as means of moral education, strengthening social relationships, and preserving cultural identity. They encapsulate life lessons and convey moral and ethical standards across generations. Furthermore, proverbs contribute to maintaining social and cultural balance within Arab communities by transmitting collective wisdom. This study highlights the close relationship between language and culture, demonstrating how proverbs foster understanding and social cohesion. Ultimately, the research underscores the importance of preserving these oral traditions in a rapidly changing world, as they provide valuable insights into the unique characteristics and values of Arab society.